The Comparison between Acute Effect of Citrullin Malate Different Doses on Aerobic and Anaerobic Power as Well as Lactate and Blood Urea Level in Young Soccer Players - Mostafa Farkhani 1, Babak; Mahdi Javadikia 1, Mahdi; Modaresi 1, Masoumeh Sadat; Mosaferi Ziaaldini 1*, Mohammad (Shahroud Journal of Medical Sciences, 2019)
Background: It has been suggested that citrulline malate (CM) is one of the effective supplements to improve exercise performance and fatigue resistance. The present study aimed to investigate the effect of consumption of CM at various doses on aerobic power, anaerobic power, as well as plasma levels of lactate and urea in young soccer players.Methods: In this semi-experimental study, performed at Ferdowsi University of Mashhad (2018), through targeted sampling, 40 trained young soccer players with were selectively classified into 4 homogenized groups based on their Vo2max value including low dose (LD) (4g), medium dose (MD) (8g), high dose (HD) (12g), and sugar solution control (C). The supplements were taken slowly within 15 minutes 1 hour prior to the tests. Then, the yoyo recovery test-level 1 and the Repeated-Sprint Ability (RSA) were used to evaluate their aerobic and anaerobic capacity, respectively. Blood biomarkers were also measured in the first 10 seconds after RSA test. Further, one-way ANOVA test was employed for data analysis. Significance level was set at 0.05.Results: The results showed that among the groups, the higher and lower values belonged to (respectively) Vo2max in HD and LD (51.13±6.22, 47.62±4.16), for RSA in HD and MD (34.11±6.34, 30.11±5.6), for urea in HD and LD (4.64±1.3, 4.16±1.46) and for lactate in C and MD (107.27±5.08, 103.66±7.34) groups (mean±S.D), respectively. There was no significant association between the groups for VO2 max value, RSA records as well as plasma levels of urea and lactate in response to taking different doses of CM (Pvalue>0.05).Conclusions: The results indicated that acute supplementation of CM at different doses did not affect aerobic and anaerobic power, or blood levels of lactate and urea.